The Origin of Stepped Rock-Cut Tunnels in Eastern Anatolia - (:unkn) unknown (PEETERS, 2018)
Stepped rock-cut tunnels are among the most interesting remains at many fortresses in Eastern Anatolia. The construction of these tunnels, which are cut deep into rock surfaces up to a length of 350 m, must have been at least as difficult as that of the fortification walls and expertise would have been required. Stepped rock-cut tunnels and associated fortresses in Eastern Anatolia have not so far been evaluated as a whole. The stepped rock tunnels in Eastern Anatolia have been accepted as one of the basic criteria indicating the Urartian period since the beginning of the 20th century. In this study, we first consider the types of stepped rock-cut tunnels in Eastern Anatolia, the purposes of their construction, and their distribution. We then discuss their dating and our interpretation of the period of their arrival in the region of Eastern Anatolia.
Keywords: Rock-cut stepped tunnel; Eastern Anatolia; Urartian Kingdom; Hellenistic-Roman Period